Public Administration and Organizational Theory: Prescribing the Proper Dose - Charbonneau, Étienne; Bromberg, Daniel; Henderson, Alexander C. (Public organization review, 2020)
Since the founding of the field of public administration, scholars have struggled with questions related to the “publicness” of public organizations (Bozeman 1987 ). In this article, the extent of this “publicness” in organizational studies research is investigated by examining articles published in the most cited journals in the disciplines of business, management, and public administration. Specifically, the analysis seeks to determine whether research in generic management journals is actually generic or if sector-specific studies remain the norm. Previous researchers have sought to answer this question using citation analysis as a preferred method. Instead, this study turns its attention to the samples employed by the articles’ authors, enabling a deeper understanding of the current state of the organizational studies scholarship. The findings suggest that a preference for public or private samples remains, and that this preference is largely dependent on the disciplinary journal in which studies were published.